Do Event-Related Evoked Potentials Reflect Apathy Tendency and Motivation? - Takayoshi, Hiroyuki; Onoda, Keiichi; Yamaguchi, Shuhei (Frontiers in Human Neuroscience, 2018)
Apathy is a mental state of diminished motivation. Although the reward system as the foundation of the motivation in the human brain has been studied extensively with neuroimaging techniques, the electrophysiological correlates of motivation and apathy have not been fully explored. Thus, in 14 healthy volunteers, we examined whether event-related evoked potentials (ERP) obtained during a simple number discrimination task with/without rewards reflected apathy tendency and a reward-dependent tendency, which were assessed separately using the apathy scale and the temperament and character inventory (TCI). Participants were asked to judge the size of a number, and received feedback based on their performance in each trial. The P3 amplitudes related to the feedback stimuli increased only in the reward condition. Furthermore, the P2 amplitudes related to the negative feedback stimuli in the reward condition had a positive correlation with the reward-dependent tendency in TCI, whereas the P3 amplitudes related to the positive feedback stimuli had a negative correlation with the apathy score. Our result suggests that the P2 and P3 ERPs to reward-related feedback stimuli are modulated in a distinctive manner by the motivational reward dependence and apathy tendency, and thus the current paradigm may be useful for investigating the brain activity associated with motivation.